Introduction to management accounting - Horngren, Charles T.; Sundem, Gary L.; Burgstahler, David; Schatzberg, Jeff (Pearson, 2022)
In todays troubled economy, its important to show students how managerial decisions can affect business costs. Introduction to Management Accounting helps to enhance students ability to make effective economic decisions by encouraging them to understand theinner-workings of the concepts, rather than solely focusing on technique memorization. Overall, this text describes both theory and common practices in a way that will help students produce information thats useful in day-to-day decision-making.
Keywords: Managerial accounting; Cost accounting; kustannuslaskenta; laskentatoimi; päätöksenteko; johtaminen; budjetointi; hinnoittelu; taloushallinto; taloussuunnittelu; kirjanpito